1993
DOI: 10.1017/s0890037x00036964
|View full text |Cite
|
Sign up to set email alerts
|

Control of Yellow and Purple Nutsedges (Cyperus esculentusandC. rotundus) in Nursery Crops

Abstract: Experiments were conducted to evaluate selective herbicides for yellow and purple nutsedge control in nursery crops. Chlorimuron at 0.03 and 0.06 kg ai ha−1suppressed yellow and purple nutsedge shoot growth either PRE or POST and did not reduce growth of barberry, Burford holly, Compacta holly, azalea, juniper, or photinia, although shoot tip chlorosis was noted in all species except Burford holly and juniper. Imazaquin at 0.25 and 0.5 kg ha−1and imazethapyr at 0.06 and 0.21 kg ha−1reduced growth of azalea. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…Similarly, mesotrione applied at 0.18 lb/acre to 0.36 lb/acre controlled yellow nutsedge 72% to 87%. This response has been reported by other researchers following bentazon or mesotrione applications for yellow nutsedge control (Armel et al, 2008;Derr and Wilcut, 1993;Fretz and Sheppard, 1979;Pereira et al, 1987;Stoller et al, 1979).…”
Section: Methodssupporting
confidence: 82%
“…Similarly, mesotrione applied at 0.18 lb/acre to 0.36 lb/acre controlled yellow nutsedge 72% to 87%. This response has been reported by other researchers following bentazon or mesotrione applications for yellow nutsedge control (Armel et al, 2008;Derr and Wilcut, 1993;Fretz and Sheppard, 1979;Pereira et al, 1987;Stoller et al, 1979).…”
Section: Methodssupporting
confidence: 82%
“…The glyphosate application rate and the plant age at the time of application influence yellow nutsedge control and viable tuber production (Appleby and Paller 1978;Keeley et al 1985;Pereira and Crabtree 1986;Stoller et al 1975). Regrowth of yellow nutsedge after an application of glyphosate at 1.1 to 2.2 kg/ha (Pereira and Crabtree 1986) and, conversely, control with glyphosate at 1.1 kg/ha or more (Derr and Wilcut 1993;Stoller et al 1975) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Cyperus species are troublesome for soybean and cotton growers in the southeastern United States because of their tolerance to many herbicides (Dowler 1998). Of the two Cyperus species that predominate in cotton and soybean, purple nutsedge is more competitive than yellow nutsedge (Cyperus esculentus L.), and there are fewer herbicides available for purple nutsedge control (Bendixen and Nandihalli 1987;Derr and Wilcut 1993;Grichar and Nester 1997;Wehtje et al 1997).…”
Section: Introductionmentioning
confidence: 99%